2013
DOI: 10.1016/j.jacc.2013.03.085
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular-Arterial Coupling, Remodeling, and Prognosis in Chronic Heart Failure

Abstract: Objectives The objective of this study was to compare the physiological determinants of ejection fraction (EF)—ventricular size, contractile function, and ventricular-arterial (VA) interaction—and their associations with clinical outcomes in chronic heart failure (HF). Background EF is a potent predictor of HF outcomes, but represents a complex summary measure that integrates several components including left ventricular size, contractile function, and VA coupling. The relative importance of each of these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
174
1
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(215 citation statements)
references
References 24 publications
(32 reference statements)
14
174
1
12
Order By: Relevance
“…Consistent with our data, the multicenter pediatric Fontan study showed that EF tended to decrease with increasing age and time post‐Fontan 2. Whereas the severity of ventricular remodeling and systolic dysfunction in the current cohort of clinically stable adult Fontan patients was less severe than that observed in similarly studied older adults with overt non‐CHD systolic HF,11 the impact of even mild systolic dysfunction may be significant in the Fontan circulation, particularly during exercise and may progress over time. Whether treatment with standard HF therapies used in non‐CHD HF patients with reduced EF would improve long‐term outcomes in adult Fontan patients remains an area of active investigation 1…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with our data, the multicenter pediatric Fontan study showed that EF tended to decrease with increasing age and time post‐Fontan 2. Whereas the severity of ventricular remodeling and systolic dysfunction in the current cohort of clinically stable adult Fontan patients was less severe than that observed in similarly studied older adults with overt non‐CHD systolic HF,11 the impact of even mild systolic dysfunction may be significant in the Fontan circulation, particularly during exercise and may progress over time. Whether treatment with standard HF therapies used in non‐CHD HF patients with reduced EF would improve long‐term outcomes in adult Fontan patients remains an area of active investigation 1…”
Section: Discussionsupporting
confidence: 88%
“…A cardiac magnetic resonance imaging study showed widely varying EDV index and EF in Fontan patients relative to controls, but did not address the relationship between remodeling and ventricular function 26. The relationship between systolic dysfunction and eccentric remodeling is consistent with typical findings in non‐CHD HF 11. LV wall thickness in Fontan patients was, on average, within normal limits, but significantly higher than in control patients.…”
Section: Discussionmentioning
confidence: 89%
“…If Anth-C increases Ea and/or reduces Ees by having a direct effect on the vasculature or myocardium, respectively, the reduction in Ea/Ees commonly observed with exercise will be greatly attenuated, indicative of reduced CVRC. Pathologic impairments in CVRC are etiologic in many chronic disease conditions [11], and surrogate measures of CVRC such as Ea/Ees are prognostic of mortality and cardiovascular events [12].…”
Section: Introductionmentioning
confidence: 99%
“…As cardiac function declines, arterial load increases to maintain systolic pressure and E es decreases, thus both lead to a decrease in this ratio representing inefficient contraction 22, 23, 24, 25, 26. Recently, this derangement has been shown to be strongly associated with adverse clinical outcomes in patients with heart failure irrespective of ejection fraction 16. To our knowledge, this is the first time that VAC is shown to be improved by cardiopulmonary rehabilitation in an unselected heart failure patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, with the introduction of noninvasive, single‐beat solutions for estimating E es ,15 it became possible to construct PV loop and assess VAC noninvasively. More important, it has been shown that VAC estimated by noninvasive methods is a strong predictor of prognosis in systolic heart failure 16. But, the effect of cardiac rehabilitation on VAC in unselected heart failure patients has not been studied thus far.…”
Section: Introductionmentioning
confidence: 99%